The role of multinationals in sparking industrialization: From 'infant industry protection' to 'FDI-led industrial take-off' - Terutomo Ozawa (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
Economic development has recently been time-compressed due to an ever-accelerating cross-border dissemination of industrial knowledge, especially at the hands of MNEs. And a new "open-door" strategy of industrial catch-up has come to be adopted, as best exemplified by China's FDI-led take-off, a strategy that is designed to capitalize on the profit-seeking activities of multinationals. This new approach needs to be conceptualized as such, replacing the time-honored conventional "closed-economy" doctrine of infant-industry protection (or import substitution).
Keywords: 330